2018
DOI: 10.1007/s00204-018-2286-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of hepatotoxicity by metabolomics: a review

Abstract: Omics technologies, and in particular metabolomics, have received an increasing attention during the assessment of hepatotoxicity in vitro. However, at present, a consensus on good metabolomics practices has yet to be reached. Therefore, in this review, a range of experimental approaches, applied methodologies, and data processing workflows are compared and critically evaluated. Experimental designs among the studies are similar, reporting the use of primary hepatocytes or hepatic cell lines as the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 115 publications
1
42
0
2
Order By: Relevance
“…As regards PK, it is important to study the absorption, distribution, metabolism, and excretion of candidate drugs in the liver, small intestine, and kidney [ 4 ]. In this context, hepatocytes and liver-derived materials are widely used in studies such as metabolite analysis (i.e., metabolomics) [ 5 , 6 ], inhibition or induction of cytochrome P450 (CYP) enzymes (at the mRNA, protein, and activity levels) [ 7 , 8 , 9 ], non-CYP enzyme metabolism [ 10 , 11 ], and prodrug metabolism [ 12 , 13 ]. On the other hand, hepatotoxicity (i.e., drug-induced liver injury, DILI) is often evaluated as part of an exploratory safety screening in the evaluation of new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…As regards PK, it is important to study the absorption, distribution, metabolism, and excretion of candidate drugs in the liver, small intestine, and kidney [ 4 ]. In this context, hepatocytes and liver-derived materials are widely used in studies such as metabolite analysis (i.e., metabolomics) [ 5 , 6 ], inhibition or induction of cytochrome P450 (CYP) enzymes (at the mRNA, protein, and activity levels) [ 7 , 8 , 9 ], non-CYP enzyme metabolism [ 10 , 11 ], and prodrug metabolism [ 12 , 13 ]. On the other hand, hepatotoxicity (i.e., drug-induced liver injury, DILI) is often evaluated as part of an exploratory safety screening in the evaluation of new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…(Lu et al, 2018;Liu and Zhong, 2019). Moreover, metabolomics can provide valuable markers for predicting DILI (Cuykx et al, 2018). Using metabolomics, Pannala et al identified the markers of acetaminophen-induced toxicity in rats, and they found that nucleotide, lipid, and amino acid metabolism were the major pathways (Pannala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…( Lu et al., 2018 ; Liu and Zhong, 2019 ). Moreover, metabolomics can provide valuable markers for predicting DILI ( Cuykx et al., 2018 ). Using metabolomics, Pannala et al.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro experiment, it can be difficult to observe drug toxicity to organs in the absence of the body’s overall regulation [ 12 , 13 ]. Mammalian models give integrated results, but the mechanism of toxicity cannot be tested [ 14 ].…”
Section: Introductionmentioning
confidence: 99%